Vivências e percepções do estágio curricular em Educação de Adultos: A perspectiva dos alunos - Oliveira, Albertina Lima; Vieira, Cristina Maria Coimbra; Alcoforado, Joaquim Luís Medeiros; Ferreira, Joaquim Armando; Simões, António (Revista Portuguesa de Pedagogia, 2009)
The goal of this study was to examine the experiences and perceptions of the students of Adult Education, through their training period in the last academic year, in what concerns to their main feelings, their supporting sources, the difficulties/obstacles faced by them, as well as the personal and external resources perceived by them. Additionally, we also tried to know if the training year has a positive effect by increasing their learning self-directedness. To develop the research it was used a combination of research strategies, both quantitative and qualitative ones, with a sample of nineteen students of the Faculty of Psychology and Sciences of Education of the University of Coimbra. Among the main results obtained, it is worthy to point out the identification of a process formed by three relatively distinct phases, during the training time, being these phases associated to specific feelings, difficulties, and resources. In what concerns to the second question of research, despite the weak tendency observed in the increasing of self-direction in learning, the results were not very consistent.